Assessment of Margin Status in Feline Mastectomy: Predictive Factors and Agreement Between Intraoperative Cytology and Histopathology - João Martins; Rute Penim; José Dos-Santos; Joana Fonseca; Pedro Faísca; Liege Martins; Nuno Leal; José Catarino; Patrícia C. Cabral; Sónia Campos (Veterinary Medicine International)
This study aimed to determine the agreement between margin status in feline mammary tumors’ surgery by comparing 3 margin assessment techniques and to determine the predictive value of prognostic clinical and histological parameters for margin status using intraoperative margin assessment techniques. During the intraoperative period, 69 surgical margins from 12 female cats undergoing unilateral radical mastectomy were assessed by imprint cytology (IC) and scrape cytology (SC), both intraoperative cytological techniques. The excised mastectomy specimens were then evaluated postoperatively by histopathology (HP). Cochran’s Q test was used to determine differences in positive margin detection for the three methods. The agreement between the three methods was assessed using the Fleiss kappa coefficient. A binary logistic regression model was used to assess whether clinical and histological prognostic parameters could predict intraoperative margin status. There was no significant difference in positive margins between the three methods (p=0.174). The agreement between the three methods was poor (Fleiss kappa = −0.020; 95% CI −0.156 to 0.117). Lymphovascular invasion is a significant predictor of a positive intraoperative margin, with an OD of 18.652 (95% CI = 1.742–199.652). These findings suggest that IC and SC are viable methods for assessing the status of surgical margins during surgery for feline mammary tumors. Intraoperative cytology may be complementary to HP, particularly in cases of lymphovascular invasion.